2006
DOI: 10.1016/s0022-5347(06)00613-6
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Androgen Receptor and Disruption of Its mRNA Expression by Exogenous Estrogens During Morphogenesis of the Genital Tubercle

Abstract: Androgen receptor protein is expressed abundantly in male and female genital tubercles. Androgen receptor mRNA levels are higher in female than in male genital tubercles through development and they increase in response to in utero ethinyl estradiol exposure with ethinyl estradiol treated females having the highest levels of expression, followed by ethinyl estradiol treated hypospadiac males. We infer that higher estrogen in genital tubercles results in a physiological response of increased androgen receptor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Therefore, future improvement in the virtual GT model should strive toward a more realistic representation of programmed cell death patterns during sexual dimorphism. The virtual GT model predicts a key role for the differential androgenized growth response of preputial (PM) versus core (CM) mesenchyme, consistent with the cellular localization of AR in vivo [3,16,17]. This effect was mediated by androgen-dependent FGF10 signaling.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Therefore, future improvement in the virtual GT model should strive toward a more realistic representation of programmed cell death patterns during sexual dimorphism. The virtual GT model predicts a key role for the differential androgenized growth response of preputial (PM) versus core (CM) mesenchyme, consistent with the cellular localization of AR in vivo [3,16,17]. This effect was mediated by androgen-dependent FGF10 signaling.…”
Section: Discussionsupporting
confidence: 54%
“…Prior to sexual differentiation, GT development is directed by a number of signaling pathways, including SHH/IHH, FGF, BMP, HOX, WNT, RAR/RXR, and ephrin/EphB2 [3,[8][9][10][11][12][13][14][15]. Subsequently, the GT develops into a male or female phenotype depending on androgen production from the fetal testis [16][17][18][19] and estrogen production from maternal and other sources [20][21][22][23]. In human populations, an increased risk of hypospadias has been associated with single nucleotide polymorphisms (SNPs) in the SHH and FGF pathways [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of several polymorphisms in AR are yet to be confirmed, with some authors reporting that an expanded CAG repeat could be relevant in isolated hypospadias [Lim et al, 2001; van der Zanden et al, 2012], whereas others found an association between the length of GGN repeats and hypospadias, especially in proximal forms [Aschim et al, 2004; Radpour et al, 2007]. These reported polymorphisms may change the ability of AR to bind testosterone rather than the levels of AR, as mouse studies have reported no direct association between changes in AR mRNA expression and the presence or absence of hypospadias [Agras et al, 2006]. …”
Section: Androgens and Hypospadiasmentioning
confidence: 88%
“…In mouse models, AR, estrogen receptor, and progesterone receptors are differentially expressed in the developing mouse genital tubercle and are responsive to exogenous estrogen (2224). Additionally, many of the environmental and pharmacologic compounds that have been associated with hypospadias signal through estrogen receptor and progesterone receptor in addition to or independent of AR (18,2432).…”
Section: Discussionmentioning
confidence: 99%